Socio-Cultural Responses of Local Communities to Tourism Infrastructure Development in Wakatobi City - Alimin Alwi; Syamsu Andi Kamaruddin; Najamuddin Najamuddin; A. Octamaya Tenri Awaru Awaru; Pacifique Mutijima (Journal of Government Science Studies, 2025)
This study aims to examine changes in the socio-cultural conditions of the people of Kapota Utara Village, South Wangi-Wangi Sub-district, Wakatobi Regency, as a result of the development of the Kapota Lake Tourism Attraction Area. The main focus of this research is on community perceptions of spatial changes, patterns of social interaction, and the sustainability of local cultural values in the context of tourism development. This research used a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and review of tourism development planning documents. The main informants consisted of community leaders, local business actors, village officials, and visitors to the tourist area. The results showed that the development of tourist areas brought significant changes to the social structure and interaction patterns of the community. There is an increase in local economic participation, but there are also concerns related to the fading of cultural values and local wisdom due to the commercialization of social space. Some communities show resistance to the influx of labor from outside the region, while others see it as a collaborative opportunity. Recommendations from this study are the importance of integrating local culture in every stage of tourism development as well as the need for participatory communication forums between the government, communities, and businesses to minimize the potential for social conflict. In addition, there is a need for cultural preservation policies through educational programs and promotion of local values that synergize with tourism development.